Perubahan Tutupan Lahan dan Kerapatan Vegetasi Mangrove di Kecamatan Siantan, Kabupaten Mempawah: Changes in Land Cover and Mangrove Vegetation Density in Siantan District, Mempawah Regency - Puji, Siti Puji Lestariningsih; Destiana; Putri, Erisa Ayu Waspadi (PERENNIAL, 2024)
One of the mangrove forests in Mempawah Regency is located in Siantan District. Mangrove forests have ecological, social, and economic functions to support the lives of living things that live around them. The extent and density of mangrove vegetation are essential parameters to determine the condition of mangroves in Siantan District to recommend rehabilitation that needs to be pursued. Data were collected from Landsat 7 images in 2010 and Landsat 8 images in 2021 with guided classification and visual interpretation to obtain a map of changes in mangrove land cover in 2010-2021. Vegetation density was obtained through Landsat Normalized Difference Vegetation Index (NDVI) analysis, divided into five density classes: very dense, dense, medium, sparse, and unvegetated. This study found that the secondary mangrove forests in Kecamatan Siantan decreased by 176.35 hectares during 2010-2021, turning into shrubs, open land, and plantations, especially in former pond areas. The most extensive deforestation turned 107.18 hectares of secondary mangrove forest into shrubs. Reforestation occurred during 2010-2021 amounted to 123.55 hectares. Natural or artificial bare land turned into 71.44 hectares of mangrove ecosystem. In 2010, the dense class dominated the mangrove forest density (60.03%) but decreased in 2021 (14.9%). A sparse class of density was not detected in 2010, but in 2021, the area of sparse density was 148.53 hectares, composed of shrubs and coconut plantations.